Representation of NLR (Neutrophil Lymphocyte Ratio) Value in Corona Virus (Covid-19) Patients by Age Group at Gatoel Mojokerto Hospital - Juliawan Apurwatama; Anik Handayati; Rinza Rahmawati (Alliance oh Health Activists (AloHA), 2024)
Currently the world is faced with the condition of the Corona virus 2019 (Covid-19) disease pandemic whose cases are still increasing over time and widespread around the world. The Covid-19 pandemic is still a health problem throughout the country, not least in Indonesia. Covid-19 is an acute respiratory disease caused by a new type of coronavirus infection or later named Severe acute respiratory syndrome 2 (SARS-CoV-2). The purpose of this study was to find out the difference in the results of neutrophil lymphocyte ratio (NLR) between Covid-19 patients with productive age and and elderly age. In Covid-19 patients with elderly age had a high NLR value above ≥3.13 with a percentage of 83% while in Covid-19 patients of productive age also had a high NLR value above ≥3.13 by 75% but the value was still lower than in Covid-19 patients with elderly age. It could be concluded that Covid-19 patients with elderly age and productive age had differences in NLR values although the same had a high NLR value above ≥3.13 and based on the results of this study in Covid-19 patients with elderly age and productive age had low lymphocyte values or experience lymphopia. Keywords: Covid-19; elderly age; productive age; neutrophil lymphocyte ratio